PERSEPSI PENDENGAR TERHADAP PROGRAM SIARAN INTERAKTIF “SORE CERIA” PADA STASIUN RRI PRO 2 FM MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This study aims to analyze the factors that influence listeners' perceptions of interactive broadcast programs and to find out what efforts are made by the RRI Pro 2 Makassar radio station to improve the quality of its programs. The type of research used in this study is a descriptive qualitative research type. Qualitative descriptive is focused on answering research questions related to the questions of who, what, where, and how an event or experience occurs until finally it is studied in depth to find patterns that emerge in the event. In short, it can be explained that qualitative descriptive is a research method that moves on a simple qualitative approach with an inductive flow. The results of this study indicate that the 'Sore Ceria' program on RRI Pro 2 Makassar has succeeded in becoming a popular radio program among young listeners thanks to its relevant content, energetic and informative announcers, and high interactivity with listeners. Despite facing challenges from digital platforms, RRI Pro 2 is committed to improving program quality through content updates, human resource development, and utilization of digital technology. This program also actively involves young people through 'Gen Masuk Siaran', which allows them to display their creativity, thereby increasing relevance and listener engagement. Going forward, the biggest challenge is to continue to innovate and adapt to changes in the media landscape, with a focus on content quality, interactivity, and the use of appropriate technology to maintain its popularity.